Answer:
25
Step-by-step explanation:
Answer:
Step-by-step explanation:
I just did this question and this was the answer that was right for me. Sorry that I saw this question late :(
Answer:
a=6
Step-by-step explanation:
Since this is a right triangle, we can use the Pythagorean theorem
a^2 + b^2 = c^2 where a and b are the legs and c is the hypotenuse
a^2 + 8^2 = 10^2
a^2 + 64= 100
a^2 +64-64 = 100-64
a^2 = 36
Take the square root of each side
sqrt(a^2) = sqrt(36)
a = 6
Answer:
a = 6
Step-by-step explanation:
According to the question,
Using Pythagorean theorem
( a )² + ( b )² = ( c )²
( a )² + ( 8 )² = ( 10 )²
evaluate the exponent
a ² + 64 = 100
subtract 64 from each side
a ² + 64 - 64 = 100 - 64
a ² = 36
Take the square root of each side
√a² = √36
a = 6
B) (-1, 2)
C) (-2, 1)
D) (-5, -3)
Answer: C (-2,1)
Step-by-step explanation:
4x2 + 14x − 7 = 0
4x2 + 26x − 10 = 0
2x2 + 2x − 10 = 0